THE EFFECTS OF MANAGERIAL CONSULTATION ON VOICE FUTILITY WITH ORGANIZATIONAL JUSTICE AS MODERATOR: MEDIATING ROLE OF PSYCHOLOGICAL SAFETY - Alyusef, Muna Ibrahim G.; Zhang, PengCheng (European Scientific Journal, ESJ, 2015)
Managerial consultation is the precursor in encouraging employee voice behaviors. In present day, voice is regarded as an essential tool in improving the performance of any organization. Employee voice acts as a driving factor in influencing organizational change and suggesting innovative ideas. Organizational justice moderates the relationship between managerial consultation and voice futility. Psychological safety motivates employees to feel safe in voicing their opinions. When employees feel they will not be treated unjustly and are free to express their ideas, they are more likely to voice their opinions without hindrance. Moreover, by anticipating positive responses from the manager, employees are more likely to have trust in management to appreciate their input. This study has three propositions. The first states that managerial consultation has a positive impact on voice futility. Secondly, organizational justice moderates this relationship while lastly, psychological safety mediates this relationship. The study concludes in the acceptance of these propositions. Researchers should explore the psychological factors of managers regarding employee voice.